Calretinin-immunoreactive neurons in the claustrum of the guinea pig. Issue 1 (15th December 2017) - Druga, Rastislav; Salaj, Martin; Edelstein, Lawrence
ABSTRACT: Background: The claustrum is present in all mammalian species. Many aspects of its morphology and function remain subject to debate. It has been suggested that calcium-binding proteins influence neuronal activity in many structures. Objective: The aim was to examine CR immunoreactivity in the claustrum of guinea pigs and compare it with that in other mammals. Design: CR immunoreactivity in the claustrum was analyzed in five guinea pigs using immunohistochemical techniques. The distribution of CR-positive neurons in the dorsal claustrum and endopiriform nucleus (END), and their morphological characteristics were described. Results: CR immunostaining in the dorsal claustrum and END of the guinea pig consisted of CR-positive neurons, fibers, and puncta of varying labeling density. The majority of these neurons displayed small- or medium-sized round, oval, and multipolar cell bodies with aspiny dendrites. CR-ir neurons prevailed in the periphery of both divisions. The dorsal claustrum was seen to have a weakly CR-ir central core surrounded by a rim of moderately positive neuropil. Conclusion: CR immunoreactivity in the guinea pig claustrum was not as diffuse as in higher mammals, but non-uniformity was evident. CR-ir neurons are distributed in both the dorsal claustrum and END, mostly in the periphery.